The Psychological Drivers of Financial Decision-Making: Enhancing Financial Literacy to Improve Personal Finance Management and Wealth Accumulation. (International Journal of Scientific Research and Management (IJSRM), 2023)
This research main objective has been to determine how psychological factors affect financial decisionmaking processes as well as individual financial behaviors are affected by psychological factors. This work aims to discuss specific psychological factors that underlie financial decisions and the importance of financial literacy to correctly approach the financial aspect and increase the level of saving and investment. The paper also seeks to analyze how some forms of cognitive bias, frame effect impact choices and emotions, self-signaling in relation to decision-making as well as self-control in managing money and illustrates how each of these factors can either have a deleterious effect or improve financial wellness. It posits that financial literacy reduces the impact of psychological biases on financial decision –making process in order to enhance the quality of financial decisions. It also provides information that can help individual, financial institutions as well as policy makers to encourage better decision making regarding financial products through informative financial education. This work specifies the psychological motives and thus explains the psychological factors inhibiting sound wealth creation and makes a point about the necessary component of personal wealth to be financial literacy.